2020
DOI: 10.1101/2020.04.14.040568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Double-targeted knockdown of miR-21 and CXCR4 inhibits malignant glioma progression by suppression of the PI3K/AKT and Raf/MEK/ERK pathways

Abstract: Background: Currently, miR-21 and CXCR4 are being extensively investigated as two unrelated key regulators in glioma malignancy. In this study, we investigated the combined effect of these two factors on glioma progression. Methods:We confirmed the expression of miR-21 and CXCR4 in malignant glioma tissue and glioma cells with qRT-PCR and western blotting. Single-targeted knockdown of miR-21 and CXCR4, as well as double-targeted knockdown of miR-21 and CXCR4 lentiviral vectors were constructed and they were tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that both the PI3K/ AKT and MEK/ERK pathways are constitutively upregulated in glioma cells, which contributes to the unrestricted growth and enhanced invasion of glioma (Liu & Yang, 2020;Loh et al, 2019). Moreover, the activation of these pathways has been confirmed to play an important role in the progression of EMT (Guo, Yao, Zhang, & Bo, 2013;Song et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have reported that both the PI3K/ AKT and MEK/ERK pathways are constitutively upregulated in glioma cells, which contributes to the unrestricted growth and enhanced invasion of glioma (Liu & Yang, 2020;Loh et al, 2019). Moreover, the activation of these pathways has been confirmed to play an important role in the progression of EMT (Guo, Yao, Zhang, & Bo, 2013;Song et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…MiR‐21 can also increase the expression of cyclin E1 and cyclin D1 in lung cancer cells, and increase the expression of CDK6 in laryngeal squamous cell carcinoma (Dai et al, 2019; Lyu et al, 2019). Of note, inhibition of miR‐21 expression in glioma has been proved to inhibit the progression of glioma (Guan et al, 2020; Liu & Yang, 2020). Consistent with previous research, we found that FXT suppressed cell viability and promoted apoptosis in glioma by downregulating miR‐21‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we also transfected ERK1/2-siRNAs into EBV positive gastric cancer cells, and the result was the same as that of adding inhibitors. The results of Liu et al showed that the doubletarget knockout of miR-21 and CXCR4 could more effectively inhibit the proliferation, migration, invasion and growth of glioma, and promote cell apoptosis, which may be related to PI3K/AKT and Raf/MEK/ERK signaling pathways [14]. CXCR4-ERK signaling pathway mediates proliferation, migration, and invasion of cancer cells in multiple types of tumors [2,15,18].…”
Section: Discussionmentioning
confidence: 99%